Pulmonary arterial hypertension in interferonophaties: a case report and a review of the literature - Trombetta, A.; Ghirardo, S.; Pastore, S.; Tesser, A.; Piscianz, E.; Tommasini, A.; Bobbo, M.; Taddio, A. (Pulmonary circulation, 2019)
Background Pulmonary arterial hypertension consists in an increase of mean pulmonary arterial pressure (PAPm ≥ 25 mmHg), and may lead to right ventricular failure. Pulmonary arterial hypertension can arise in several disorders, encompassing inflammatory conditions and connective tissue diseases. The occurrence of pulmonary arterial hypertension has recently been reported in monogenic interferonopathies and in systemic lupus erythematosus, highlighting the pathogenic role of type I interferons and paving the way to therapies aimed at inhibiting interferon signaling. Case We describe a 17-year-old boy with DNase II deficiency, presenting a clinical picture with significant overlap with systemic lupus erythematosus. During treatment with the Janus kinase inhibitor ruxolitinib, he developed pulmonary arterial hypertension, raising the question whether it could represent a sign of insufficient disease control or a drug-related adverse event. The disease even worsened after drug withdrawal, but rapidly improved after starting the drug again at higher dosage. Summary and conclusion Pulmonary arterial hypertension can complicate type I interferonopathies. We propose that ruxolitinib was beneficial in this case, but the wider role of Janus kinase inhibitors for the treatment of pulmonary arterial hypertension is not clear. For this reason, a strict cardiologic evaluation must be part of the standard care of subjects with interferonopathies, especially when Janus kinase inhibitors are prescribed.